1987
DOI: 10.1109/tec.1987.4765873
|View full text |Cite
|
Sign up to set email alerts
|

On the Choice of Phase-Balancer Capacitance for Induction Motors Fed from Single-Phase Supply

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The subject matter has been extensively discussed in the literature [2][3][4][5][6][7], with the main goal having been to provide a balanced three-phase excitation for the stator windings of the machine.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The subject matter has been extensively discussed in the literature [2][3][4][5][6][7], with the main goal having been to provide a balanced three-phase excitation for the stator windings of the machine.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely adopted voltage-balancing technique is to connect a capacitor, referred hereafter to as the voltage-balancing capacitor, across two of the stator terminals [2]. It can be shown that the most balanced three-phase voltage is achieved with a unique capacitance, referred (in [2]) to as the optimum capacitance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations